TetriBee using Artificial Bee Colony algorithm on Tetris - Riños, Jonnah Lyn; Lagorra, Clint Anthony (2010)
Tetris is a very popular decision-making puzzle video game of falling blocks. The goal is to make a horizontal line out of the placed blocks from a randomly generated falling block. Playing Tetris optimally has been proven to be NP-complete. That is, it cannot be solved with polynomial time. Artificial Bee Colony algorithm, a swarm intelligence based on the foraging behavior of honey bee swarm, it is used to find an optimized solution. In evaluating a board's state, an evaluation function was used to choose the best move. This evaluation function is a weighted linear combination of all the 19 features. Results show that ABC algorithm is a feasible approach in finding an optimal solution that will best play a given set of Tetraminoes. Moreover, results show that ABC is capable of achieving its maximum number of cleared lines nearest to the theoretical best.
Undergraduate thesis (B.S. Computer Science) -- University of the Philippines, Tacloban.
Keywords: Puzzles; Tetris; Swarm optimization; Artificial Bee Colony algorithm